Three-Subject Game Based Economic Optimization of Integrated Energy System for Carbon-Green Certificate Trading - Ma, Xinru; Dong, Jian; Lu, Xinyi; Tang, Xiaomin; Guo, Zhizhen; Wang, Haixin; Yang, Junyou; Hu, Shiyan (2024 IEEE 8th Conference on Energy Internet and Energy System Integration (EI2), 2024)
To reduce the carbon emission level and improve the operation economy of the system, an integrated energy system (IES) optimization operation model is proposed. First, combined with the green certificate trading mechanism, the model of the stepped carbon trading mechanism and the stepped green certificate trading mechanism is constructed. Second, three-subject game model of the integrated energy retailer (IER) as the leader, energy producer (EP) and load aggregator (LA) as the followers is constructed. Finally, three-subject game-based economic optimization of integrated energy system in carbon-green certificate trading markets mechanism is verified by an example, and the benefits of objective functions IER, EP and LA are maximized. Simulations are presented to validate the reasonableness and effectiveness of the proposed model.